Analysis of an application degree of marketing in organization and management activity of youth sports schools - N.V. Sereda (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Disclosed aspects of the marketing approach in the activities of youth sports schools. The degree of use of marketing in the organization and management of youth sports schools. Identified constraints and the possible consequences of the use of marketing in youth sports schools. The study involved 127 employees with 15 youth sports schools. The respondents were the director and deputy instructor methodists that senior coaches offices youth sports schools. It is certain that in their professional activities only 36.0% of workers in youth sports schools use marketing is the marketing research, 73.2% of respondents believe that the use of marketing to promote the image of youth sports schools. The absence of a marketing specialist in the management bodies of physical education and sport is one of the main problems for the efficient functioning of the market of sports schools sports and sports services.